Hydrogen bonding mediated orthogonal and reversible self-assembly of porphyrin sensitizers onto TiO2 nanoparticles - Zeininger, Lukas; Lodermeyer, Fabian; Costa Riquelme, Rubén Dario; Guldi, Dirk Michael; Hirsch, Andreas (Chemical Communications, 2016)
We report on the orthogonal, highly directional and reversible self-assembly of porphyrins onto TiO2 nanoparticles by means of hydrogen bonding interactions. Unifying the stable covalent surface attachment of tailored, synthesized Hamilton receptors with the advantages of a non-covalent supramolecular immobilization of porphyrin cyanurates resulted in a redox- and photo-active nanohybrid. The latter was successfully implemented into a new type of supramolecular dye-sensitized solar cells.